The Effectiveness of Facebook Advertisements on Purchase Intention of Customers in Malaysia - Mahmud, Shah Roman Al (South Asian Journal of Social Sciences and Humanities, 2020)
The purpose of this empirical study is to examine the effectiveness of Facebook advertisement on  enhancing consumer purchase intention. Facebook, as a social networking site, has become very  popular among the people of all ages around the world. Facebook advertising is becoming very popular  as it can reach to the mass people as a medium of social sites. The study is hopefully help Facebook  stakeholder provide their customers with more customized messages and offer rewards and promotions  to encourage them for exposing their products and services.
Keywords: Facebook Advertisement; Activity; Brand Loyalty; EWOM; Purchase intention